Performance of Holstein-Friesian calves drinking desalinated water in the preweaning period - Ventura-Ríos, Joel; Domínguez-Díaz, David; Lara-Bueno, Alejandro; Villalobos-Villalobos, Guillermo; López-Ordaz, Rufino; Jaimes-Jaimes, José; Ruíz-Flores, Agustín (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: High salinity of drinking water can adversely affect health and productive performance of calves during artificial rearing. Objective: To evaluate the effect of drinking water total dissolved salts (TDS) content on productive performance of Holstein-Friesian calves during artificial rearing. Methods: Twenty-nine newborn Holstein-Friesian calves weighing 39±0.94 kg at birth were randomly assigned to two treatment groups for 56 d. Treatment 1 (n=14) consisted of drinking water with 1,469±75 mg L-1 TDS, while treatment 2 (n=15) used drinking water from the same source but filtered by reverse osmosis to contain 107±31 mg L-1 TDS. Results: Water intake was numerically affected by TDS concentration, increasing 13% (p>0.08) when drinking low-TDS water (3,554 versus 3,088 ml d-1). Feed intake (dry basis) decreased 26% (500 versus 676 g d-1; p<0.05), and average daily weight gain increased 29% (434 versus 335 g d-1; p<0.05) for calves drinking low-TDS water. Treatment 2 resulted in 10% higher body weight compared to treatment 1 (64.3 versus 58.6 kg; p<0.01). Digestibility of dry matter and protein was not affected (p>0.05) by TDS content in the drinking water. Conclusion: Desalinated water improves productive performance of Holstein-Friesian calves during artificial rearing.